Food Stamps and the Working Poor - Mueser, Peter (W.E. Upjohn Institute, 2019)
The authors show that many households that are eligible for food stamps do not receive them, and that eligible individuals' enrollment is influenced by the states' administrative requirements. Highlighted are the procedures for certifying applicants and recertifying recipients, and policies for treatment of able-bodied adults without dependents.